A randomised phase II trial testing the acceptability and feasibility of a narrative approach to public health communication to increase community engagement with palliative care. (September 2020) - Collins, Anna; McLachlan, Sue-Anne; Hill, Mike; Collins, Sue; Philip, Jennifer
Background: Communities have limited understanding of palliative care, creating barriers to informed choice around consideration of a full range of care options in the event of serious illness. Few empirically tested interventions are available to educate community about palliative care, and ultimately improve timely access to these services. Aim: To test the acceptability (primary outcome), and feasibility of a narrative approach to public health communication seeking to improve attitudes to possible access to palliative care in the event of serious illness. Design: Randomised phase II trial with six parallel experimental conditions. Outcomes tested included measures of acceptability, feasibility and change in attitudes to possible access to palliative care post-intervention. Contrasts planned for exploratory testing included format, message content and narrator. Setting/participants: Community-based sample of consecutive English-speaking adults who volunteered their participation in response to a study advertisement distributed online through established community groups. Results: A narrative approach to public health communication was found to be acceptable to community members, and feasible to deliver online. Exploratory data suggested it immediately improved attitudes towards possible access to palliative care in the event of serious illness, with the narrative detailing a description of the evidence delivered by a healthcare professional appearing to be the most promising strategy. Conclusions: This study provides preliminary data to inform a future, longitudinal trial evaluating effectiveness and ultimately other evidence-based, public health approaches to improve community engagement with palliative care. Further studies are required to confirm the generalisability of findings to a broader representative sample and other settings including internationally.